2023
DOI: 10.1128/spectrum.02426-22
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Pollution Impacts Soil Bacterial Community Structure and Antimicrobial Resistance at the Birmingham 35th Avenue Superfund Site

Abstract: Heavy metals cross-select for antimicrobial resistance in laboratory experiments, but few studies have documented this effect in polluted soils. Moreover, despite decades of awareness of heavy metal contamination at the EPA Superfund site in North Birmingham, Alabama, this is the first analysis of the impact of this pollution on the soil microbiome.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Overall, the ambient permafrost community comprised taxa commonly found in permafrost, soil and sediments, including Chloroflexi (Solirubrobacterales and KD4-96), Actinobacteriota (Gaiellales, Micrococcales, Microtrichales), and Rhizobiales (Costello & Schmidt, 2006;Gołębiewski et al, 2014;Goswami et al, 2023;Liu et al, 2022;Zhang et al, 2019). The ambient seawater microbiome was typical for pelagic marine waters, dominated by SAR11, Flavobacteriales and Pseudomonadales (e.g., SAR86, SAR92).…”
Section: Degradation Of Ancient Organic Matter Is Mediated By Both Am...mentioning
confidence: 99%
“…Overall, the ambient permafrost community comprised taxa commonly found in permafrost, soil and sediments, including Chloroflexi (Solirubrobacterales and KD4-96), Actinobacteriota (Gaiellales, Micrococcales, Microtrichales), and Rhizobiales (Costello & Schmidt, 2006;Gołębiewski et al, 2014;Goswami et al, 2023;Liu et al, 2022;Zhang et al, 2019). The ambient seawater microbiome was typical for pelagic marine waters, dominated by SAR11, Flavobacteriales and Pseudomonadales (e.g., SAR86, SAR92).…”
Section: Degradation Of Ancient Organic Matter Is Mediated By Both Am...mentioning
confidence: 99%
“…These organisms showed a propensity for soils with reduced carbon/nutrient availability (Shange et al, 2012) and are also widespread with high abundance in HM-polluted soils (Navarro-Noya et al, 2010;Gołębiewski et al, 2014;Yan et al, 2016;Salam and Varma, 2019). Recently, Goswami et al (2023) reported a positive correlation between this taxon and Zn and Pb concentration. Interestingly, the group has been identified as an indicative taxon in HM-contaminated mining and agricultural soils (Huang et al, 2021) and similarly demonstrated to associate with metal-accumulating plants and are easily enriched in HMsupplemented agricultural soils (Wu et al, 2021;Kuo et al, 2018).…”
Section: Frontiers In Environmental Sciencementioning
confidence: 99%